Fungsi keuntungan Cobb-Douglas dalam pendugaan efisiensi ekonomi relatif - Indah Susantun (Economic Journal of Emerging Markets, 2000)
Researchers of agricultural economics use much the Cobb-Douglas profit function as a one of quantitative methods. This article examines it to analyze economic efficiency in term of technical and price efficiency in the casa of fermented soybean cake industry as a member and non member of cooperative (KOPTI).